Effect of Cloud computing technology adoption on Reduction in Costs: A critical review from the perspective of business - et. al., Rajesh Gharpure, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital technologies have significantly contributed towards enabling organizations achieve business excellence objectives. Among technologies that most organization pursue to achieve these goals of performance and flexibility; cloud computing has emerged as a front runner in recent years. Cloud computing technology has a significant effect on organizational performance, and this can lead to improvement in the financial performance as well. This paper aims to presents the effect of adopting Cloud computing technology on reduction in costs from the business perspective. The review findings show that the most perceived benefits of cloud computing are realized through cost savings. However, there is an observed lack of well-defined methodology to accurately estimate cost reduction benefits accruing through cloud technology adoption for an organization. Therefore, it is suggested that further research should be attempted to establish methods to estimating the cost reductions leading to higher profit margins and better financial performance of organizations.